Perlindungan Hukum Bagi Konsumen Terhadap Hidden Fees Praktik Periklanan Menyesatkan di Sektor Perbankan Digital - Fitrianto, Bambang; Hardianto, Hardianto; Surbakti, Join Yordan; Marbun, Jessica Oktari; Sari, Mutia (Sharia Journal and Education Center Publishing, 2026)
The rapid development of information technology and the digitalization of banking services have significantly transformed the delivery of financial products, particularly through digital banking platforms. While digital banking offers efficiency and convenience, it also gives rise to legal issues related to consumer protection, especially concerning the imposition of hidden fees through misleading advertising practices. Hidden fees are costs that are not transparently disclosed to consumers at the initial stage of product promotion, causing consumers to make financial decisions based on incomplete or inaccurate information. In the context of banking law, such practices raise serious legal concerns regarding transparency, fairness, and the accountability of banks toward consumers. The Indonesian legal framework has incorporated consumer protection principles, including the obligation of transparency, good faith, and prohibition of misleading advertising in banking services. However, regulatory arrangements specifically governing hidden fees in digital banking advertisements remain fragmented and lack explicit enforcement mechanisms, potentially leading to legal uncertainty and consumer vulnerability. This study aims to analyze the legal protection afforded to consumers against hidden fees arising from misleading advertising practices in the digital banking sector. The research employs a normative legal method using statutory and conceptual approaches by examining banking regulations, consumer protection laws, and legal doctrines related to transparency and liability. The findings indicate that banks may be held legally liable when hidden fees result from misleading advertisements, insufficient disclosure of costs, or violations of the principles of transparency and good faith. Therefore, clearer and more comprehensive legal regulation is necessary to strengthen consumer protection and ensure legal certainty in digital banking practices.